1H NMR Profiling of Honey Bee Bodies Revealed Metabolic Differences between Summer and Winter Bees - Lee, Saetbyeol; Kalcic, Filip; Duarte, Iola F; Titera, Dalibor; Kamler, Martin; Mrna, Pavel; Hyrsl, Pavel; Danihlik, Jiri; Dobes, Pavel; Kunc, Martin; Pudlo, Anna; Havlik, Jaroslav (Insects, 2022)
In temperate climates, honey bee workers of the species Apis mellifera have different lifespans depending on the seasonal phenotype: summer bees (short lifespan) and winter bees (long lifespan). Many studies have revealed the biochemical parameters involved in the lifespan differentiation of summer and winter bees. However, comprehensive information regarding the metabolic changes occurring in their bodies between the two is limited. This study used proton nuclear magnetic resonance (1H NMR) spectroscopy to analyze the metabolic differences between summer and winter bees of the same age. The multivariate analysis showed that summer and winter bees could be distinguished based on their metabolic profiles. Among the 36 metabolites found, 28 metabolites have displayed significant changes from summer to winter bees. Compared to summer bees, trehalose in winter bees showed 1.9 times higher concentration, and all amino acids except for proline and alanine showed decreased patterns. We have also detected an unknown compound, with a CH3 singlet at 2.83 ppm, which is a potential biomarker that is about 13 times higher in summer bees. Our results show that the metabolites in summer and winter bees have distinctive characteristics; this information could provide new insights and support further studies on honey bee longevity and overwintering.
Keywords: metabolome; winter bees; nuclear magnetic resonance; Apis mellifera; longevity